AMP-activated protein kinase is involved in perfluorohexanesulfonate -induced apoptosis of neuronal cells. (April 2016) - Lee, Youn Ju; Choi, So-Young; Yang, Jae-Ho
Abstract: Perfluorohexanesulfonate (PFHxS), one of the major perfluoroalkyl compounds (PFCs), has been used in a variety of industrial and consumer applications and detected in serum in the general population. This raised a concern over its possible detrimental health effects, including neurotoxic effects. We have previously shown that PFHxS induced neuronal apoptosis via the NMDA receptor-mediated extracellular signal-regulated kinase (ERK) pathway. Recently, it has been reported that AMP-activated protein kinase (AMPK) acts as a key signal molecule in neuronal excitotoxicity as well as providing a neuroprotective function. In the present study, we have examined the involvement of AMPK in PFHxS-induced neuronal apoptosis using neuronal differentiated PC12 cells. PFHxS induced significant increases in intracellular [Ca 2+ ] via the NMDA receptor and the L-type voltage-gated calcium channel (L-VGCC). The inhibition of Ca 2+ loading by the NMDA receptor antagonist, MK801 and the L-VGCC blockers, nifedipine and diltiazem significantly reduced PFHxS-induced apoptosis. PFHxS induced sustained activation of AMPK and the inhibition of AMPK activation by compound C and AMPK siRNA significantly reduced PFHxS-induced caspase-3 activity. These results indicate the pro-apoptotic role of AMPK. The activation of AMPK was attenuated by MK801, nifedipine and diltiazem. However, the activation of AMPK was not affected by the ERK inhibitor, PD98059. Likewise, ERK activation was not affected by compound C but was substantially reduced by MK801, nifedipine or diltiazem. This suggests that the activation of AMPK and ERK is regulated by intracellular Ca 2+ loading in distinct pathways. Taken together, PFHxS-induced neuronal apoptosis is mediated by AMPK and ERK pathways, which are distinctly regulated by increased intracellular Ca 2+ via the NMDA receptor and L-VGCC. Highlights: Ca 2+ influx via NMDA receptor and L-type calcium channel is involved in PFHxS-induced apoptosis of PC12 cells. PFHxS-induced apoptosis of PC12 cells is AMPK- and ERK- dependent. AMPK and ERK are downstream molecules of increased intracellular Ca 2+ . AMPK and ERK activation are regulated by distinct pathways.